Enhancing drought resistance in Pogostemon cablin (Blanco) Benth. through overexpression of ACC deaminase gene using thin cell layer regeneration system - Warsi, Zafar I.; Khatoon, Kahkashan; Singh, Pooja; Rahman, Laiq Ur (Frontiers in Plant Science, 2023)
The Pogostemon cablin cultivation faces massive constraints because of its susceptible nature to drought stress that reduces patchouli propagation and oil yield. The present study has achieved an efficient and rapid direct regeneration system for transgenic production of P. cablin using Agrobacterium-mediated genetic transformation. To establish an efficient regeneration protocol for fast in-vitro multiplication of patchouli plants, leaf, petiole, and transverse thin cell layer (tTCL) explants were used and inoculated on an MS medium supplemented with different combinations of phytohormones. A comparative study showed a maximum regeneration frequency of 93.30 ± 0.56% per explant was obtained from leaf segments on optimal MS medium fortified with 0.2mg/L BAP and 0.1mg/L NAA. Leaf and petiole explants took 25-35 days to regenerate while tTCL section showed regeneration in just 15-20 days on the same medium. Subsequently, productive genetic transformation protocol OD600 0.6, AS 200µM, 30mg/L kanamycin, and infection time 5 min. was standardized and best-suited explants were infected at optimum conditions from the Agrobacterium tumefaciens (LBA 4404) strain harbouring ACC deaminase to generate transgenic P. cablin Benth. (CIM-Samarth) plants. The investigation suggested that the optimized protocol provides a maximum transformation frequency of 42 ± 1.9% in 15-20 days from tTCL. The transgenic plants were shifted to the greenhouse with a 52.0 ± 0.8% survival frequency. A molecular docking study confirmed significant binding affinity of ligand ACC with ACC deaminase at the catalytic site, and ligand interactions showed four H-bonds at the binding pocket with amino acids Cys-196, Val-198, Thr-199, and Gly-200 that validate gene relative expression in transgenic plants. Among all transgenic acclimatized greenhouse-grown patchouli plants, line PT4 showed improved drought resistance under severe water stress as its RWC was 71.7 ± 2.3% to 75.7 ± 2.1% which is greater than the RWC of control plant, 58.30 ± 0.21%. Analysis of the other physiological indicators, H2O2, chlorophyll content and ROS result support drought resistance ability. Our study concluded that the first report on P. cablin, tTCL direct regeneration and standardized transformation protocol created a new opportunity for genetic manipulation to achieve drought-resistant patchouli plants for cultivation in all seasons at the commercial level.